2018
DOI: 10.1002/jcad.12190
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Posttraumatic Stress Disorder Checklist (PCL)

Abstract: In this systematic review, the authors analyzed 336 published articles and dissertations that used the Posttraumatic Stress Disorder Checklist (PCL) to determine the reliability and validity of scores on 3 different versions: PCL–Specific, PCL–Military, and PCL–Civilian. Results confirmed Weathers, Litz, Herman, Huska, and Keane's () claim that the PCL has adequate psychometric properties and appears to support the construction of a new version, the PCL‐5, as a population‐nonspecific instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 106 publications
(238 reference statements)
0
24
1
1
Order By: Relevance
“…Total severity scores, as well as clinically significant, are generated by summing all items. A review of 135 studies including the PCL-C indicated that the measure demonstrated excellent internal consistency across studies (α = 93) [43]. Higher PCL-C scores suggest worse symptom severity.…”
Section: Demographic Questionnairesmentioning
confidence: 99%
“…Total severity scores, as well as clinically significant, are generated by summing all items. A review of 135 studies including the PCL-C indicated that the measure demonstrated excellent internal consistency across studies (α = 93) [43]. Higher PCL-C scores suggest worse symptom severity.…”
Section: Demographic Questionnairesmentioning
confidence: 99%
“…The authors chose a cut-off score of 44. However, there is no universal validated threshold score to make a diagnosis with the PCL-C, as cut-offs vary between 27 and 59 2. Nydegger et al suggested using a score of 50 or more to indicate PTSD in a firefighting population 3.…”
Section: Dear Editormentioning
confidence: 99%
“…The study looked into only male firefighters, with women being excluded from the study. Evidence shows that PTSD is twice as prevalent in women as in men 2. Although the exact mechanisms behind the development of PTSD are unknown, animal studies have shown there to be gender-specific neurochemical changes following exposure to trauma 4.…”
Section: Dear Editormentioning
confidence: 99%
“…These short‐forms are limited, though, either because they were developed using heuristic methods, or in the case of computer‐adaptive testing, cannot be used with paper and pencil administration. Furthermore, research on the comparative performance of the different short‐form PCLs is limited (Tiet, Schutte, & Leyva, ), creating uncertainty about the optimal number and content of items (Bressler, Erford, & Dean, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research on the comparative performance of the different short-form PCLs is limited (Tiet, Schutte, & Leyva, 2013), creating uncertainty about the optimal number and content of items (Bressler, Erford, & Dean, 2018).…”
mentioning
confidence: 99%